Climate change is predicted to cause population collapse in a cooperative breeder - Daniella Rabaiotti; Tim Coulson; Rosie Woodroffe (Global Change Biology, 2023)
It has been suggested that animals may have evolved cooperative breeding strategies in response to extreme climatic conditions. Climate change, however, may push species beyond their ability to cope with extreme climates, and reduce the group sizes in cooperatively breeding species to a point where populations are no longer viable. Predicting the impact of future climates on these species is challenging as modelling the impact of climate change on their population dynamics requires information on both group‐ and individual‐level responses to climatic conditions. Using a single‐sex individual‐based model incorporating demographic responses to ambient temperature in an endangered species, the African wild dog Lycaon pictus , we show that there is a threshold temperature above which populations of the species are predicted to collapse. For simulated populations with carrying capacities equivalent to the median size of real‐world populations (nine packs), extinction risk increases once temperatures exceed those predicted in the best‐case climate warming scenario (Representative Concentration Pathway [RCP] 2.6). The threshold is higher (between RCP 4.5 and RCP 6.0) for larger simulated populations (30 packs), but 84% of real‐world populations number